Biomarkers of ocular manifestation in newly diagnosed giant cell arteritis - Terheyden, Jan H.; Petzinna, Simon M.; Burg, Lara C.; von der Emde, Leon; Behning, Charlotte; Jungblut, Julie; Reinking, Katharina; Holz, Frank G.; Ach, Thomas; Wintergerst, Maximilian W. M.; Schäfer, Valentin S.; Finger, Robert P. (BMC ophthalmology, 2025)
Giant cell arteritis (GCA) is a vasculitis of large and medium-sized vessels that causes severe ophthalmic complications. Timely diagnosis and disease monitoring may prevent permanent vision loss but biomarkers for early ocular involvement are scarce. This study evaluates early optical coherence tomography (OCT) and OCT angiography (OCTA) biomarkers of ocular involvement in newly diagnosed GCA. Newly diagnosed GCA patients and similarly aged controls were enrolled. Participants underwent ocular examination, including OCT and OCTA imaging of the macula and optic disc. OCT metrics included macular ganglion cell layer (GCL) and peripapillary retinal nerve fiber layer (pRNFL) thickness. OCTA parameters included vessel density (VD), vessel skeleton density, and vessel diameter index (VDI). Associations between imaging biomarkers and GCA symptoms (ordinal GCA symptom score) were analyzed using age-adjusted regression models. We recruited 23 newly diagnosed GCA patients and 27 controls. VD and VDI in the deep retinal capillaries were significantly higher in GCA compared to controls (p ≤ 0.027). In patients reporting ocular symptoms, GCL thickness, volume and pRNFL thickness were increased in 11%, 22% and 17% of Early Treatment Diabetic Retinopathy Study subfields compared to controls (p ≤ 0.04). Additionally, GCL and pRNFL thicknesses were associated with GCA symptoms (p ≤ 0.041). OCT and OCTA imaging revealed structural and perfusion alterations in newly diagnosed GCA patients. Retinal microcirculation was altered, even regardless of the presence of ophthalmic symptoms. Structural changes correlated with systemic manifestations of GCA, suggesting a link between extracranial and intracranial involvement. Our findings underscore the potential diagnostic value of OCT and OCTA biomarkers for ocular involvement in GCA.